Microbiological analysis of a synbiotic gut health supplement capsule by metagenomics - Vivek N. Upasani; Shiva S. Chettiar; Alpesh R. Patel; Devendrasinh D. Jhala; Harsh Mistry (European Journal of Biological Research, 2025)
Probiotics i.e. the use of living microorganisms for health benefits has been known since ancient times. There is an increasing awareness and concern among the consumers, regulators, medical fraternity, researchers, etc. about these products/supplements formulated to contain single or more beneficiary microorganisms. These microbes may be beneficial independently or synergistically for an individual’s health by protecting against pathogens, reduce metabolic disorders and boost immunity. Nowadays, next generation probiotics are being developed with microbial strains isolated from humans (gut or stool) or genetically engineered microbes for treating specific health condition. Gut microbiome studies have also helped in developing probiotics with novel microorganisms. Synbiotics are products containing prebiotics and probiotics. Food safety agencies provide guidelines to characterize and identify the microbial strains and their role in such products. Traditional, rapid identification and molecular methods as well as clinical trials are included to justify the efficacy and safety of the probiotics and related products. We report here the 16S metagenomics study on a synbiotic supplemental capsule available online containing twenty-five bacterial species. These results reveal the presence of a consortia of bacteria containing many species not mentioned on the product label. It also provides some insights for testing of these products using molecular tools for regulatory purpose.